A Code that Simulates Fast-Ion D_Alpha and Neutral Particle Measurements (Communications in Computational Physics, 2011)
A code that models signals produced by charge-exchange reactions betweenfast ions and injected neutral beams in tokamak plasmas is described. With the fastiondistribution function as input, the code predicts the efflux to a neutral particleanalyzer (NPA) diagnostic and the photon radiance of Balmer-alpha light to a fastionDα (FIDA) diagnostic. Reactions with both the primary injected neutrals and withthe cloud of secondary "halo" neutrals that surround the beam are treated. Accuratecalculation of the fraction of neutrals that occupy excited atomic states (the collisional-radiativetransition equations) is an important element of the code. Comparison withTRANSP output and other tests verify the solutions. Judicious selection of grid sizeand other parameters facilitate efficient solutions. The output of the code has beenvalidated by FIDA measurements on DIII-D but further tests are warranted.